Yifei Sanjie Formula or Placebo With Anlotinib as Second-Line or Above Treatment for Metastatic Non-Small-Cell Lung Cancer: Study Protocol for a Double-Blind, Placebo-Controlled Randomized Pilot Study - Wenmin Chen MM; Jietao Lin MD; Ting Yang MM; Ze xin Zhang MM; Lanting Tao MD; Zhiwei Xiao MD; Hanrui Chen MM; Xiangjun Qi MM; Lingling Sun MD; Yang Cao MD; Lizhu Lin MD (Integrative Cancer Therapies, 2023)
Background: Anlotinib is used as a third-line treatment for advanced non-small-cell lung cancer (NSCLC), but has limited clinical benefits and several side effects, such as diarrhea and acneiform skin rash. Traditional Chinese Medicine (TCM) is commonly used to treat cancers in China. Chinese herbal medicines may have the potential as adjuvant therapies to reduce toxicity and improve the efficacy of treatments for NSCLC. Given the positive outcomes of basic research, we plan to evaluate whether the addition of the Chinese herbal medicine Yifei Sanjie formula (YFSJF) to anlotinib can improve the progression-free survival (PFS) of advanced NSCLC patients. Methods: A multicenter, randomized, double-blind, placebo-controlled parallel-group controlled pilot trial will be performed. Forty eligible patients will be randomized in a ratio of 1:1 to the intervention (YFSJF + anlotinib) and control (placebo + anlotinib) groups. Participants will be advised to take 12 mg/day of anlotinib on days 1 to 14 of each 21-day cycle. YFSJF or placebo will be administered (15 g twice daily) during each cycle until progression of disease (PD). The primary outcome will be progression-free survival (PFS), and the secondary outcomes will be overall survival (OS), the objective response rate (ORR), and patient-reported outcomes (PRO). Tumors will be assessed based on RECIST v. 1.1 after every 2 cycles of treatment. The M. D. Anderson Symptom Inventory-Lung Cancer (MDASI-LC) will be used to evaluate PRO at baseline and weekly thereafter until PD. Discussion: This will be the first trial to evaluate the effectiveness and safety of TCM combined with anlotinib for the treatment of NSCLC. The results of this randomized controlled trial will fill a gap in the research by showing whether YFSJF combined with anlotinib can improve PFS in NSCLC patients. Trial Registration: The study was registered on June 8th, 2021 on Chinese Clinical Registry; registration number ChiCTR2100047143. ( https://www.chictr.org.cn/index.aspx ). Ethics and Dissemination: The Ethics Committee of the First Affiliated Hospital of Guangzhou University of Traditional Chinese Medicine approved the study protocol (approval no.: K2020151, 2021/08/19). The study will also be supervised and managed by the Ethics Committee.